The Relevance and Implications of Livestock-tree Interactions in Agroforestry Systems in Developing Countries - Devendra, C (Annals of Arid Zone, 2016)
Livestock-based agroforestry systems present important opportunities for increasing food production from farm animals. This is reflected in the widening gap between production and consumption, and the inability of domestic supplies to meet projected demand for foods of animal origin up to year 2020. Increasing productivity from animals thus necessitates assessment of all possible avenues of food production, including agroforestry systems. In South-east Asia alone, this concerns an estimated 210 million hectares under permanent tree crops and forests. The livestock-tree interactions include animal draught power for land cultivation and crop growth; effects of dung and urine on soil fertility and crop growth; use of crop residues and agro-industrial by-products; use of native vegetation on cost of weed control; effects of integrating livestock with trees, and that of the shade of trees on animal performance; and type of production systems on crop performance and environmental protection. Case studies are presented, data from which clearly demonstrate positive benefits, economic and ecological impacts. Areas for research include characterization of livestock-based agroforestry systems in target agro-ecological zones; compatibility between livestock and trees; appropriate choice of livestock species, production systems, and optimum age of trees for integration with livestock; effects of dung and urine and nutrient recycling on soil fertility and crop yields; efficient use of crop residues and agro-industrial by-products ill situ; and assessment of the nature, extent and implications of the interactions. Increased resource use and concerted research focus on livestock-based agroforestry systems can provide for demonstrable improved efficiency in the management of natural resources, sustainable production systems, and increased productivity from the land in the future.